2018
DOI: 10.1039/c8cc01155a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free site selective cross-coupling of pyridines with secondary phosphine chalcogenides using acylacetylenes as oxidants

Abstract: Pyridines undergo site selective cross-coupling with secondary phosphine chalcogenides (oxides, sulfides, and selenides) in the presence of acylphenylacetylenes under metal-free mild conditions (70-75 °C, MeCN) to afford 4-chalcogenophosphoryl pyridines in up to 71% yield. In this new type of SNHAr reaction acylacetylenes act as oxidants, being stereoselectively reduced to the corresponding olefins of the E-configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…In 2018, Trofimov and co‐workers found that pyridines easily underwent site‐selective cross‐coupling with secondary phosphine chalcogenides in the presence of acylphenylacetylenes under mild conditions to give 4‐chalcogenophosphorylated pyridines in up to 71% yield . The acylphenylacetylenes acted as oxidants, being reduced to the corresponding E ‐configured olefins in this new type of S N H Ar reaction.…”
Section: Direct Phosphorylation Of the Parent Heterocyclesmentioning
confidence: 99%
“…In 2018, Trofimov and co‐workers found that pyridines easily underwent site‐selective cross‐coupling with secondary phosphine chalcogenides in the presence of acylphenylacetylenes under mild conditions to give 4‐chalcogenophosphorylated pyridines in up to 71% yield . The acylphenylacetylenes acted as oxidants, being reduced to the corresponding E ‐configured olefins in this new type of S N H Ar reaction.…”
Section: Direct Phosphorylation Of the Parent Heterocyclesmentioning
confidence: 99%
“…In 2018, it was found that the regioselective oxidative cross-coupling reaction between pyridines 1a,b and secondary phosphine chalcogenides 2a-j was triggered and further driven by electrophilic acetylenes 3a-d to produce S N H products, phosphorylated pyridines 4a-n, and E-acylphenylethenes 5a-d (Scheme 1) [37]. The reaction tolerates a quite representative number of structurally diverse secondary phosphine chalcogenides (oxides, sulfides and selenides), having both aromatic and alkyl aromatic substituents.…”
Section: One-step S N H Phosphorylationmentioning
confidence: 99%
“…The reaction tolerates a quite representative number of structurally diverse secondary phosphine chalcogenides (oxides, sulfides and selenides), having both aromatic and alkyl aromatic substituents. The reaction involves the reversible generation of 1,3-dipole A via a nucleophilic attack of pyridine nitrogen at the electron-deficient triple bond (Scheme 2) [37].…”
Section: One-step S N H Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations